2015
DOI: 10.3390/foods4030318
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phytone Peptone to Optimize Growth and Cell Density of Lactobacillus reuteri

Abstract: The objective of this study was to determine the use of phytone peptone to optimize the growth and cell density of Lactobacillus reuteri. Four strains of L. reuteri (DSM 20016, SD 2112, CF 2-7F, and MF 2-3,) were used in this study. An overnight culture of individual strains was inoculated into fresh basal media with various protein sources (peptone, tryptone, proteose peptone #3, phytone peptone, tryptic soy broth, yeast extract, and beef extract). Samples were then mixed well and incubated at 37 °C for 15 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
1
20
1
Order By: Relevance
“…Previously, we found that phytone peptone (PP) is the most important growth-promoting factor for Lactobacillus reuteri (Atilola, Gyawali, Aljaloud, & Ibrahim, 2015). Our results indicate that DPM supplemented with PP support the growth of L. reuteri.…”
Section: Discussionsupporting
confidence: 54%
“…Previously, we found that phytone peptone (PP) is the most important growth-promoting factor for Lactobacillus reuteri (Atilola, Gyawali, Aljaloud, & Ibrahim, 2015). Our results indicate that DPM supplemented with PP support the growth of L. reuteri.…”
Section: Discussionsupporting
confidence: 54%
“…rhamnosus E/N [ 33 ] and L . reuteri [ 38 ]. Hebert et al [ 39 ] showed that Tween 80 had different effects on the growth of several LAB: it has stimulated L .…”
Section: Discussionmentioning
confidence: 99%
“…This ingredient was developed as an alternative nitrogen source in dehydrated culture media to accommodate various nutritional requirements of LAB. Other non-animal protein sources such as phytone peptone have also been shown to support the growth of LAB (Atilola et al ., 2015). Phytone peptone is an ultra-filtered enzymatic digest of soybean meal and has a high buffering capacity that helps to maintain the pH level during the fermentation process.…”
Section: Standard Mediamentioning
confidence: 99%
“…This protein has been shown to enhance growth and increase the cell mass of Lb. reuteri (Atilola et al ., 2015). The primary ingredient in M17 is tryptone peptone which is a pancreatic digest of casein that is recommended for the rapid growth and detection of microorganisms present in low concentrations.…”
Section: Standard Mediamentioning
confidence: 99%